2010
DOI: 10.1002/jat.1590
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intracellular signalling by insulin and the hypermitogenic AspB10 analogue in MCF‐7 breast adenocarcinoma cells

Abstract: We compared mitogenicity and intracellular signalling by human insulin and the AspB10 (X-10) human insulin analogue in MCF-7 human mammary adenocarcinoma cells. By flow analysis of phosphorylated histone H3 or cell cycle distributions, insulin and X-10 were mitogenic at physiologically relevant concentrations (2 nm to 74 pm range), with X-10 being approximately 3-fold more mitogenic than insulin. By western blotting with phospho-specific antibodies, insulin induced phosphorylation of IRS-1, Akt, p70S6K, S6 rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Differences between in vitro and in vivo potency of AspB10 have been previously described (35) and highlight the need for caution when interpreting the results of in vitro studies. In vivo studies have not previously demonstrated whether AspB10 exerts its mitogenic effects through the IR or IGF-IR (21,25). Understanding the mechanism through which AspB10 promotes tumor growth is important for the development of new insulin analogs to ensure they are not mitogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between in vitro and in vivo potency of AspB10 have been previously described (35) and highlight the need for caution when interpreting the results of in vitro studies. In vivo studies have not previously demonstrated whether AspB10 exerts its mitogenic effects through the IR or IGF-IR (21,25). Understanding the mechanism through which AspB10 promotes tumor growth is important for the development of new insulin analogs to ensure they are not mitogenic.…”
Section: Discussionmentioning
confidence: 99%
“…An asymmetrical preferential phosphatidylinositol 3-kinase (PI3K) pathway activation and, specifically, stimulation of protein translation, was seen after stimulation with insulin X10 [29]. Other studies have also found an important role of the PI3K pathway [25], whereas yet more results seem to favour a more pronounced stimulation of the extracellular signal-regulated kinase (ERK) pathway [30].…”
Section: Understanding Insulin X10mentioning
confidence: 97%
“…The possibility that insulin analogues have a different effect on the incidence of cancer than human insulin, has been a reason for concern since the 1990s, when the clinical development of the rapid-acting analogue AspB10 had to be terminated because of the risk for malignancies - an effect attributed to a lower dissociation rate from the insulin receptor and/or to a higher affinity for the IGF-1 receptor (23). Glargine also has a greater affinity for the IGF-1 receptor than human insulin, producing a greater proliferative effect in vitro (24).…”
Section: Evidence Acquisitionmentioning
confidence: 99%